EFFECTS OF ENVIRONMENTAL AND WATER QUALITY VARIATIONS ON HEMATOLOGICAL PARAMETERS OF NILE TILAPIA (Oreochromis niloticus) REARED IN POND AND RECIRCULATING AQUACULTURE SYSTEMS - Nushrat Jahan; Mohammad Abu Baker Siddique; Imran Bin Younos; Ilias Ahmed; Md Shiekh Tauhiduzzaman Shimul; Safiara Nusrat Nova; Balaram Mahalder; Mohammad Mahfujul Haque; Mariom Mariom; A. K. Shakur Ahammad (Indonesian Aquaculture Journal, 2026)
Aquaculture is crucial for global food security, yet environmental change threatens fish health, particularly in freshwater species like Nile tilapia (Oreochromis. niloticus). This study aimed to evaluate the effects of environmental and water quality variations on the hematological responses of Nile tilapia reared in outdoor pond systems and indoor Recirculating Aquaculture Systems (RAS). The study was conducted over a 12-month duration (June 2023 to May 2024) using three replicate outdoor earthen ponds and three indoor RAS tanks. Daily data regarding environmental variables were collected from the government Meteorological Department, while water quality parameters were monitored on-site daily and biological sampling was conducted four times monthly.  Tilapia managed within the RAS system exhibited higher mean RBC counts (1.512 × 10v /mL), which may be  associated with improved oxygen availability and stable environmental conditions, while outdoor pond fish showed higher mean WBC (389.188 × 10³/mL) and elevated glucose (122.675 mg/dL) level, potentially reflecting physiological or immunological responses to fluctuating environmental conditions. All hematological parameters differed significantly between systems (p < 0.05). RAS maintained more stable water quality, with higher DO (8.53 mg/L vs. 7.03 mg/L in ponds, p < 0.001) and zero ammonia, though TDS was higher (242.301 ppm, p = 0.034). Pond environments experienced greater temperature fluctuations, with rainfall contributing to reduction in pH. Environmental and water quality variables strongly shaped hematological responses, highlighting their role in fish welfare. Environmental and water quality variables showed measurable associations with hematological responses, highlighting their potential influence on fish welfare. The findings suggest that RAS may support improved environmental stability and physiological condition through controlled water quality management, with potential implications for fish health, broodstock quality, and sustainable aquaculture development.